(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Short-wave diathermy (SWD) is an electrotherapeutic modality used in the conservative treatment of knee osteoarthritis (KOA). To evaluate the effectiveness of shortwave diathermy (SWD) in context to our physical, social, occupational and socioeconomic condition adjuvant to other treatment option for knee osteoarthritis (OA). Methods: 80 patients aged 49-65 with KOA were randomized into two groups. One group (n=40) was treated with SWD (thrice in a week for six weeks), NSAIDs (naproxen 250 mg), Activity of Daily Living (ADL), Exercise (Quadriceps strengthening exercise), the other (n=40) with NSAIDs, ADL, Exercise. Patients were assessed before treatment and at every week interval for six weeks. Outcome measures included visual analogue scale (VAS) for knee pain, Western Ontario and McMaster University Osteoarthritis Index (WOMAC) and range of Motion (ROM). Results: There was highly significant improvement (P<0.001) observed in group A patient (83.81%) compared to group B (69.70%) in visual analogue scale, also in WOMAC score it is seen highly significant improvement (P<0.001) in group A patient (87.49%) compared to group B (79.37%). Comparison of range of motion in goniometer there was not showed significant improvement between groups A (18.06%).and group B (21.81%). Conclusion: SWD is effective in management of pain in OA knee joint and thus improve patient functional outcome. SWD is helpful to reduce the symptoms of chronic OA-knee joints and decrease the necessary of intake of NSAIDs and thereby side effects of NSAIDs may be reduced.